Early Detection of Colour Blindness Using Video Games - Dawson-Howe, Kenneth (SCITEPRESS, 2026)
This paper presents research into the detection of colour blindness in children and young adults through the use of modified video games. Existing gamification in this area has primarily considered very young children (under 7) and so more advanced games are necessary for the attention of older children and young adults. Initial testing with 50 participants shows significant potential for the detection of colour blindness using adapted retro games
21st International Conference on Computer Vision Theory and Applications
PUBLISHED
Marbella, Spain
Keywords: Computer Vision Application; Colour Blindness; Computer Graphics & Vision; Computer Science; Visual impairment; Health; Youth